Analysis of factors causes schools drop out: Case study for Children in the Mabar Hilir - Khairunnisa Cahyani; Yusnadi; Muhammad Takwin Machmud (PT. Global Research Collaboration, 2024)
This study is aiming to determine the factors causing children to drop out of school in Mabar Hilir environment, which is useful for providing educational teaching is very important to reduce school dropout rates. This study uses a qualitative methodology that includes interviews, observation, and a descriptive approach. Children who had dropped out of school in Village Mabar Hilir served as respondents for this study. This study collects respondent data using interview instruments. According to the research's findings, one children who should have been in school at that age was not attending, and twelve students had dropped out. There are several main reason that causing this phenomena including economics and environment factors.